THE INFLUENCE OF A REGULAR GYMNASTICS PROGRAM IN ELDERLY WOMEN (Fiep Bulletin - online, 2014)
The objective of this study was to analyze the influence of a 16-week gymnastics program over some physical aptitude and health indicators, as well as analyze the behavior of these indicators after a 12-week interruption of this program.  The target subjects were made up of 12 volunteer ladies, aged 60 to 69 years old, who resided in the city of Marechal Cândido Rondon.  The program lasted 4 months and had 3 weekly classes of 1 hour each.  There were 3 tests during this period.  The analyzed variables were the body mass index - (IMC, in Portuguese), systolic and diastolic artery pressure and flexibility.  The collected data were analyzed by the SPSS for Windows® version 8.0 program.  A descriptive statistic was utilized by means of an average calculation and of standard deviation.  For the inferential statistics a variance analysis was used.  After the analyses of the tests, we noticed that these ladies reduced the values for the IMC.  The Arterial Pressure presented a drop in values during the program and it increased again after the interruption of the program.  As far as the flexibility is concerned, the increase was also satisfactory because they reached the advisable level of 27 to 34 cm.  Based on the results, we concluded that the proposed physical exercises had a positive influence over the Arterial Pressure, IMC and flexibility because the gymnastics favored the performance of the aforementioned items.  We also noticed that these ladies started to develop awareness about the importance that physical activity presents in relation to physical aptitude and health.